2022
DOI: 10.1155/2022/3863138
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Dose-Dependent Cytotoxicity Profile of Gracilaria edulis-Mediated Green Synthesized Silver Nanoparticles against MDA-MB-231 Breast Carcinoma

Abstract: Green-based synthesis of metal nanoparticles using marine seaweeds is a rapidly growing technology that is finding a variety of new applications. In the present study, the aqueous extract of a marine seaweed, Gracilaria edulis, was employed for the synthesis of metallic nanoparticles without using any reducing and stabilizing chemical agents. The visual color change and validation through UV-Vis spectroscopy provided an initial confirmation regarding the Gracilaria edulis-mediated green synthesized silver nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…After treatment with PTAgNPs, the A431 cells were re-suspended in ice-cold PBS [ 51 ]. In a glass slide, approximately, 10,000 cells in a volume of 100 mL were coated with a thin layer ona 1.0% ( w / v ) agarose frosted glass slide and covered with a coverslip and incubated in cold condition for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…After treatment with PTAgNPs, the A431 cells were re-suspended in ice-cold PBS [ 51 ]. In a glass slide, approximately, 10,000 cells in a volume of 100 mL were coated with a thin layer ona 1.0% ( w / v ) agarose frosted glass slide and covered with a coverslip and incubated in cold condition for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…7 a,b). Similarly, Mohanta et al 69 reported that the IC 50 values for biosynthesized GE-AgNP treatment were significantly lower in MDA-MB-231 cells than in L-929 cells after exposure for 24 or 48 h. Also, the biosynthesized AgNPs using Pyrostegia venusta leaf aqueous indicated significantly increased cytotoxic activity against COS-7 cells in vitro, with IC 50 value of 50.48 µg/mL 70 . Heidari et al 71 reported that Thymus vulgaris L. extract possesses less toxicity (70% cell mortality) on T47D breast cancer cells than biosynthesized AgNPs (90% cell mortality).…”
Section: Discussionmentioning
confidence: 84%
“…For determination of MIC were concentrations of ZnO NPs (31.255μg /mL, 62.5μg /mL, 125μg/mL, 250μg/mL, 500μg /mL) incubated all these tubes at 37°C for 24 hr, with dark conditions, MIC is a lowest ZnO nanoparticles concentration that inhibited completely the bacterial growth and can detected and determined the concentration of tube first one 125μg/mL with to be the Minimum inhibitory concentration [18].…”
Section: Determination Of Minimum Inhibitorymentioning
confidence: 99%